Restoration through formalization? Assessing the potential of Peru's Agroforestry Concessions scheme to contribute to restoration in agricultural frontiers in the Amazon region. (September 2016) - Robiglio, Valentina; Reyes, Martin
Highlights: Expansion of AFS and adoption of conservation practices are at the basis of CUAF allocation. Forest landscape restoration can benefit of the implementation of CUAF. To be successful, CUAF need to acknowledge farmers' heterogeneity. To be successful, CUAF need transectorial coordination among key implementing actors. Abstract: Agroforestry Concessions are an innovative legal provision of the Forest Law of Peru. Granted to farmers at the agricultural frontier and conditioned on the compliance with the maintenance of tree cover and the adoption of agroforestry and soil and water conservation practices, Agroforestry Concessions have the potential of a win-win option to meet country pledges to 20 × 20 Restoration Initiative. The case study, conducted in one of the oldest deforestation frontier of Amazon, shows that the pathway for this mechanism to succeed starts from the recognition of local agroforestry practices including fallow-based systems and the understanding of the shift in farmers' livelihoods this mechanism might require.